The Effect of Pellet Made from Mixture of Maggot Flour, Mealworm Flour, And Golden Snail Flour on Growth of Cherax quadricarinatus - Subchan, Wachju; Azzahra, Syarafina; Prihatin, Jekti (BIOEDUKASI, 2023)
Feed is one of the main points that determine crayfish successful cultivation. The feed commonly use fish flour tends to be expensive; therefore, it becomes an obstacle for crayfish cultivators. This study aimed to determine the effect of pellet feed made from maggot flour, mealworm flour, and golden snail flour on crayfish growth as an alternative feed that are more affordable. This research was conducted using laboratory experiment design consisted of three treatments and three replications of each. The research design used fish flour-based pellet for control (P0), maggot flour, mealworm flour, and golden snail flour-based pellet for treatment 1 (P1), maggot flour, mealworm flour, golden snail flour, and fish flour-based pellet for treatment 2 (P2). The experiment conducted during one month, using 90 individuals’ crayfish. The effect of treatments on the growth measured by three main parameters such as: dry and wet biomass, carapace length, and supported by feed analysis using feed conversion ratio (FCR) and feed utilization efficiency (FUE). The results showed that P1 has significant effect on the dry biomass growth (p=0.001), wet biomass growth (p=0.000), carapace length growth (p=0.049). Feed analysis showed that P1 has significant effect on FCR (p=0.004) and FUE (p=0.010).